Ethnobotanical studies of wild edible plants in some regions of Azerbaijan - Gurbanova, Lala (Ethnobotany Research and Applications, 2025)
Background: Before the advent of agriculture, people survived relying on wild plants found in nature. Most of the wild plants that are important for food are wild edible plants. In times of economic crises, wild edible plants came to the aid of the population. During wars, the population consumed dishes prepared from both the underground and aboveground parts of wild edible plants, including raw plant parts. Methods: The research was conducted using ethnobotanical materials personally collected by the author during surveys in various regions of Azerbaijan, especially among the older generation. Field studies were conducted in villages across 14 regions and the ethnobiological knowledge of local population were recorded. A total of 349 people were interviewed during these surveys. The frequency of citation (FC) of each plant species reported by local communities was calculated and the resulting data were analyzed using Relative Frequency of Citation (RFC). Results: The taxonomic analysis of wild edible plants in the biodiversity of the geographical regions of Azerbaijan revealed the distribution of 119 species belonging to 97 genera, grouped into 2 classes and 36 families. In terms of species distribution, the Asteraceae family occupies the leading position with 13 genera (13%) and 13 species (11%); followed by Apiaceae family with 11 genera (11%) and 11 species (9%); Brassicaceae family with 12 genera (12%), 12 species (10%); Lamiaceae family with 10 genera (10%), 10 species (8,4%); Polygonaceae family with 3 genera (3%), 10 species (8.4%). The majority of the flora in the study area consists of 80 (67%) perennial species. The remaining species are annuals-26 (22%), biennials-11 (9%), semi-shrubs -1 (1%) and lianas-1 (1%). Vegetable characteristics, collection times and ethnopharmacological properties in folk medicine have been documented for 13 species of the Asteraceae family, 11 of the Apiaceae family, 12 of the Brassicaceae family, 10 of the Lamiaceae family and 10 of the Polygonaceae family. The commodity forms were identified for 30 species of economic importance: 24 species are sold fresh , 6 species are preserved salted and 10 species are sold dried. Conclusions: During the research, ethnobotanical data on plants were collected. It should be noted that a significant part of the material collected through oral information is quickly forgotten, and its preservation in written form is considered one of the key priorities. Analysis of the collected materials revealed that to identify the patterns of distribution of individual plant species across the region, it is important first toexamine the interaction of human activity with vegetation. Information on the use of individual plant species was obtained both from local knowledge and field surveys. Keywords: Ethnobotany, Folk medicine, Local population, Edible plant